2020
DOI: 10.14740/jocmr4098
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tofogliflozin on Cardiac Function in Elderly Patients With Diabetes Mellitus

Abstract: Background: Patients with type 2 diabetes mellitus (T2DM) are at increased risk for impairments in diastolic relaxation and heart failure with preserved ejection fraction (EF). Recent clinical data suggest that several sodium glucose transporter-2 (SGLT2) inhibitors are found to reduce cardiovascular disease (CVD) events in elderly diabetic patients, but the effect of tofogliflozin, one of the SGLT2 inhibitors, on CVD is unknown. We retrospectively investigated the effect of tofogliflozin on cardiac function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
3
6
0
Order By: Relevance
“…The present study found that LV diastolic function as measured by E/e' for patients with T2DM had significantly improved 3 months after administration of tofogliflozin in elderly patients with T2DM, consistent with the previous results [ 14 - 16 ]. Other cardiac functional parameters such as diameter of LAD and IVCmax did not change 3 months after administration of tofogliflozin.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study found that LV diastolic function as measured by E/e' for patients with T2DM had significantly improved 3 months after administration of tofogliflozin in elderly patients with T2DM, consistent with the previous results [ 14 - 16 ]. Other cardiac functional parameters such as diameter of LAD and IVCmax did not change 3 months after administration of tofogliflozin.…”
Section: Discussionsupporting
confidence: 93%
“…The present study found that LV diastolic function as measured by E/e' for patients with T2DM had significantly improved 3 months after administration of tofogliflozin in elderly patients with T2DM, consistent with the previous results [14][15][16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…SGLT2 inhibitor-induced plasma volume reduction and hemoconcentration leading to improvement of oxygen transport could contribute to the efficient myocardial energetics. Indeed, SGLT2 inhibitors including tofogliflozin significantly improve left ventricular diastolic function in patients with T2DM [45,47]. It remains unclear whether there are differences in cardiac effects between agents belonging to this class of drugs, while a clinical comparison of tofogliflozin and empagliflozin based on a 48-week retrospective analysis showed that empagliflozin had a significantly stronger effect on the hematocrit than tofogliflozin [48].…”
Section: Effects Of Tofogliflozin On Glucose Metabolism and Other Parmentioning
confidence: 99%
“…In this study the improvement in diastolic function was independent of E, but attributable to reduced early diastolic left ventricular relaxation and paralleled by a reduction in LVMI 22 . Furthermore Higashikawa et al reported Tofogli ozin to improve E/e' in 42 elderly patients with diabetes 23 .…”
Section: Discussionmentioning
confidence: 99%